Occurrence and avoidance of liquid metal embrittlement in resistance spot welding of springback-afflicted deep-drawn components - Biegler, Max; Yang, Keke; Meschut, Gerson; Rethmeier, Michael (Science and Technology of Welding and Joining)
This study investigates the occurrence and mitigation of liquid metal embrittlement occurring during resistance spot welding in deep-drawn automotive components, specifically focusing on an S-Rail made from advanced high-strength steel. A simulation-based liquid metal embrittlement risk criterion based on local major component stresses was established and used to quantify and compare liquid metal embrittlement risks between different tests. Experimental and numerical analyses were conducted, revealing that springback significantly impacts liquid metal embrittlement formation. Adjustments in electrode geometry and hold time post-welding were found to mitigate liquid metal embrittlement risks. The effects of stack-up configuration and related parameter settings on liquid metal embrittlement occurrence were identified and liquid metal embrittlement was effectively prevented across both stack-up configurations. These findings advance the understanding of liquid metal embrittlement mechanisms and provide practical approaches to enhance the spot weld quality in AHSS-based body-in-whites.

Die Ausbildung von morgen gestalten: mit 5G und für 5G. - Koppius, Sebastian Niklas; Beutner, Marc; Krings, Sarah Claudia; Schäfers, Johannes; Temmen, Katrin; Sauer, Stefan; Pieper, Carsten; Schuba, Kornelia

Students’ performance and typical errors in filling empty probabilistic visualizations with probabilities or frequencies - Rößner, Michael; Binder, Karin; Geier, Corbinian; Krauss, Stefan (Educational Studies in Mathematics)
Abstract It has been established that, in Bayesian tasks, performance and typical errors in reading information from filled visualizations depend both on the type of the provided visualization and information format. However, apart from reading visualizations, students should also be able to create visualizations on their own and successfully use them as heuristic tools in modeling tasks. In this paper, we first want to broaden the view on Bayesian reasoning to probabilistic tasks with two binary events in general and embed the whole process of solving these tasks using probabilistic visualizations in a modified modeling framework. Thereby, it becomes apparent that most of the steps remained untouched by existing research. Second, in the present empirical study, we focused on one part of the largely unexplored creation process and examined entering statistical information into empty visualizations as heuristic tools. N = 172 participants had to enter conditional and joint probabilities or the corresponding frequencies into empty visualizations in a paper-and-pencil test. We analyze (a) students’ performance when entering information in visualizations and (b) typical errors, both dependent on the information format (probabilities vs. natural frequencies), which empty visualization structure (2⨯2 table, double tree, net diagram) was provided, and type of information (conditional vs. joint information). The well-known positive effect of natural frequencies on participants’ performance was evident when entering conditional information into 2⨯2 tables and net diagrams. However, with respect to joint information, no superior effect of frequencies was observed. Furthermore, the theoretical implementation of our research in a modeling cycle allows us to identify desiderata for future research.

„Die Erde ist eine Scheibe und wir waren nie auf dem Mond!“? Ein Seminar zur Nature of Science und Techniken der Wissenschaftsleugnung - Webersen, Yvonne; Riese, Josef (Entdecken, lehren und forschen im Schülerlabor. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bochum 2024)

Toward high-density streptavidin arrays on DNA origami nanostructures - Rabbe, Lukas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (RSC Advances)
Streptavidin binding to DNA origami-supported high-density biotin arrays is investigated for selected experimental parameters. While bidentate binding and steric hindrance can be minimized, molecular crowding limits the binding yields in 2D arrays.

Westfalenspott/Westfalenlob vom Humanismus bis zum 17. Jahrhundert. Mit einem Ausblick auf die Wirkung in der Moderne - Süßmann, Johannes (775 — Westfalen. Das Buch. Eine Region wird gemacht. Begleitband zur Ausstellung im LWL-Museum in der Kaiserpfalz Paderborn, 16. Mai 2025–1. März 2026)

Der Begriff der Religion im ersten deutschen Fremdwörterbuch von 1571 - Süßmann, Johannes

Students’ personality impacts sense of belonging of students in different ways - Bohndick, Carla; Breetzke, Jonas; Klingsieck, Katrin B.; Buhl, Heike M. (Social Psychology of Education)

Symmetries of various sets of polynomials - Seguin, Beranger Fabrice (Beiträge zur Algebra und Geometrie)
Let $K$ be a field of characteristic $0$ and $k ≥ 2$ be an integer. We prove that every $K$-linear bijection $f : K[X] → K[X]$ strongly preserving the set of $k$-free polynomials (or the set of polynomials with a $k$-fold root in $K$) is a constant multiple of a $K$-algebra automorphism of $K[X]$, i.e., there are elements $a, c \in K^{×}$, $b \in K$ such that $f(P)(X) = c P(a X + b)$. When $K$ is a number field or $K=\mathbb{R}$, we prove that similar statements hold when $f$ preserves the set of polynomials with a root in $K$.

Blogpost: "Praxisseminar zur Konzeption und Publikation eines wissenschaftlichen Sammelbands" - Spener, Anna Maria

SoTL und Forschung in der Religionspädagogik - Reis, Oliver (Scholarship of Teaching and Learning und disziplinäre Forschung: Eine komplexe Beziehung)

Entwicklung fachdidaktischen Wissens zum Einsatz digitaler Medien im Fach Physik - Große-Heilmann, Rike Isabel

World War and World Peace in the Age of Digital Capitalism - Fuchs, Christian

Präferenzen beim Gebrauch von Konklusionsmarkern im Französischen und im Deutschen - Kunert, Irene Dorothea (Lexikologie, Phraseologie, Semantik kontrastiv. Romanisch-deutsche und innerromanische Streifzüge)

Passiv genderkompetente Lehrkräfte - Richter, Susanne (Beiträge zur Schulentwicklung)

La famille de Neuveforge comme lien entre Pays-Bas et Saint-Empire. Partie ii - Huybrechts, Yves; Di Pillo, Théo (BeNeLuxNet)
L’article précédent explore les liens institutionnels et diplomatiques entre les Pays-Bas espagnols et le Saint-Empire romain germanique aux XVIe et XVIIe siècles. À travers une structure politique complexe et morcelée, le Saint-Empire incarne le principe de souveraineté partagée, tandis que les territoires bourguignons, sous domination espagnole, cherchent à préserver leur rôle au sein de l’Empire via le Cercle de Bourgogne. La montée en puissance de Louis XIV et sa politique d’expansion fragilisent cet équilibre, forçant les diplomates espagnols à renforcer les alliances impériales, bien que ces tentatives soient souvent entravées par les divisions internes du Reich. Les guerres successives, jusqu'à la Ligue d'Augsbourg et le traité de Ryswick, illustrent les tensions entre ambitions nationales et équilibre européen, dans lesquelles les diplomates comme les Neuveforge jouent un rôle essentiel.

Liens et défis entre Pays-Bas espagnols et Saint-Empire romain germanique. Partie i - Huybrechts, Yves; Di Pillo, Théo (BeNeLuxNet)
Cet article explore en trois parties le rôle crucial de la famille Neuveforge dans la relation entre les Pays-Bas espagnols et le Saint-Empire romain germanique à la fin du XVIIe siècle, dans le contexte de la Guerre de la Ligue d'Augsbourg et des ambitions expansionnistes de Louis XIV. En tant que juristes influents siégeant au Reichstag, ils jouent un rôle clé dans les négociations visant à récupérer la ville et la forteresse stratégique de Luxembourg pour l’Espagne. Grâce à leur statut social, leur maîtrise des langues et leur expertise juridique, ils manœuvrent habilement face aux Français. La trajectoire des Neuveforge illustre ainsi l’influence déterminante des diplomates et juristes dans les relations entre les Pays-Bas et l’Empire, au cœur d’une Europe en pleine tourmente. Nous aborderons ce sujet en trois parties. Dans cette première partie, nous aborderons la nature générale et les problèmes des relations entre les Pays-Bas espagnols et l'Empire.

La famille Neuveforge : une influence diplomatique concrète. Partie iii - Huybrechts, Yves; Di Pillo, Théo (BeNeLuxNet)
L’article précédent retrace le rôle diplomatique de la famille Neuveforge, originaire du Luxembourg, qui sert de lien entre les Pays-Bas espagnols et le Saint-Empire romain germanique au XVIIᵉ siècle. Actifs à la Diète de Ratisbonne, Louis et Jean Henri de Neuveforge négocient pour protéger les intérêts des Habsbourg, notamment la reconquête du Luxembourg, stratégique mais capturé par Louis XIV en 1684. Leur maîtrise du droit, des langues étrangères et des subtilités des titulatures nobiliaires s’avère essentielle dans un contexte où chaque mot peut influer sur les rapports de pouvoir. À travers leurs efforts, la famille Neuveforge illustre l'importance de la diplomatie dans un ordre européen marqué par la compétition entre France, Espagne et Empire.

Determinants of primary school students’ support and their attitudes towards peers with social and emotional difficulties. - Löper, Marwin Felix; Hellmich, Frank (Research on Preschool and Primary Education)

Lipsius, ein katholischer Antimachiavelli? - Huybrechts, Yves; Sanders, Joshua (BelgienNet)
Wie soll man glücklich sein und sich damit zufriedengeben, von Ungerechten beherrscht zu werden? Wenn diese Ungerechten zudem untereinander Kriege führen, unter dessen Auswirkungen man leidet, ohne dass man die Möglichkeit hätte einzugreifen? Wer kann in dieser Ohnmacht noch Glück finden? Und an die Herrscher gefragt: Wie muss der ideale Politiker sein? Hierauf wollte Justus Lipsius Antworten anbieten. Die Bedeutung dieser Fragen, die auch heute noch relevant sind, wird aus seiner eigenen Zeit heraus nochmal präsent. Lipsius lebte nämlich in Zeiten intensiver politischer und vor allem religiöser Konflikte, welche seine Biografie in mehreren Punkten berühren. Er musste nicht nur mehrmals vor Konflikten fliehen, sondern seine Werke wurden auch äußerst kritisch von der Kirche und den Landesherren betrachtet. In diesem Beitrag wird zunächst kurz der Werdegang Lipsius‘ geschildert, bevor auf zwei seiner wichtigsten Werke und deren Einfluss auf die Staatslehre jener Zeit eingegangen wird.